Many Labs 5: Registered Replication of Payne, Burkley, and Stokes (2008), Study 4. Issue 3 (September 2020) - Ebersole, Charles R.; Andrighetto, Luca; Casini, Erica; Chiorri, Carlo; Dalla Rosa, Anna; Domaneschi, Filippo; Ferguson, Ian R.; Fryberger, Emily; Giacomantonio, Mauro; Grahe, Jon E.; Joy-Gaba, Jennifer A.; Langford, Eleanor V.; et al.
To rule out an alternative to their structural-fit hypothesis, Payne, Burkley, and Stokes (2008) demonstrated that correlations between implicit and explicit race attitudes were weaker when participants were put under high pressure to respond without bias than when they were placed under low pressure. This effect was replicated in Italy by Vianello (2015), although the replication effect was smaller than the original effect. In the current investigation, we examined the possibility that the source of a study's sample moderates this effect. Teams from eight universities, four in the United States and four in Italy, replicated the original study (replication N = 1, 103). Although we did detect moderation by the sample's country, it was due to a reversal of the original effect in the United States and a lack of the original effect in Italy. We discuss this curious finding and possible explanations.